Innovative Approaches in Working with Children with Psychological Barriers - Mamatqulova Dinora (Scientific Trends, 2025)
Children with psychological barriers face complex challenges in learning, communication, and socialization. Traditional pedagogical and therapeutic approaches, while valuable, are often insufficient in addressing the diverse needs of this group. This paper explores innovative approaches—including digital technologies, art-based therapy, inclusive pedagogy, cognitive-behavioral methods, and family-centered models—that can foster resilience, creativity, and integration of children with psychological barriers into educational and social environments. The study adopts a mixed-method approach, combining theoretical analysis, case studies, and evaluation of contemporary practices in inclusive education and developmental psychology. Findings highlight the significance of early intervention, technology-enhanced learning, and interdisciplinary collaboration. The discussion emphasizes sustainability, cultural sensitivity, and ethical considerations in applying innovation to child development. The article contributes to advancing modern psychology and pedagogy by offering an evidence-based framework for educators, psychologists, and policymakers.
Keywords: Psychological barriers, children, innovation, inclusive education, therapy, digital learning, resilience, developmental psychology.